Safety and Efficacy of Tenofovir Alafenamide Fumarate in Early-Middle Pregnancy for Mothers With Chronic Hepatitis B - Chen, Ruochan; Zou, Ju; Long, Liyuan; Huang, Haiyue; Zhang, Min; Fan, Xuegong; Huang, Yan (Frontiers in Medicine, 2022)
Background Tenofovir alafenamide fumarate has been used in late pregnancy; however, no data exist regarding its safety and effectiveness in early and middle pregnancy for mothers with hepatitis B virus infection. Aims To design a prospective study to investigate the efficacy and safety of TAF in pregnant women with chronic HBV infection during early-middle pregnancy. Methods Pregnant women with active chronic hepatitis B who received tenofovir alafenamide fumarate during early and middle pregnancy were enrolled and followed up until 6 months postpartum. Infants received immunoprophylaxis. The primary endpoint was the safety of mothers and infants. The secondary endpoints were maternal hepatitis B virus DNA reduction at delivery and mother-to-child transmission rate. Results Among 98 mothers enrolled, 31 initiated tenofovir alafenamide fumarate in early pregnancy, and 57 in middle pregnancy. The mean (± standard deviation) age was 29.00 (±3.81) years. At delivery, 100% (98/98) of the mothers achieved hepatitis B virus DNA levels <200,000 IU/L. Ninety-eight infants were born, and none had congenital defects or malformations. All infants received hepatitis B virus immunoprophylaxis. The mother-to-child transmission rate was 0%. Growth parameters including body weight, height, and head circumference were comparable to the national standards for physical development. No severe adverse effects were reported in either mothers or infants. No severe liver function damage occurred in any of the mothers. Conclusions Initiating tenofovir alafenamide fumarate in early and middle pregnancy appears safe for both mothers and infants, and it is effective for controlling maternal disease as well as interrupting mother-to-child transmission.